Study of turbidity treatment in Karangpilang II Water Treatment Plant - Arief Rahman; Ali Masduqi (Sustinere: Journal of Environment and Sustainability, 2017)
Karangpilang II Water Treatment Plant (WTP) is part of the Karangpilang WTP of Surabaya Water Utilities, serving the water supply needs of Surabaya City. Karangpilang II WTP has the largest clean water production capacity within the Karangpilang WTP, reaching 2,500 L/s. Using conventional treatment to remove turbidity, the treatment process in Karangpilang II WTP consists of pre-sedimentation, clearator, and filter units.This study evaluated turbidity levels in production water and the efficiency of turbidity removal to assess the performance of Karangpilang II WTP in turbidity treatment. The evaluation was conducted using 2016 data by comparing the turbidity of production water with the Water Quality Standards of the Water Utilities, as well as by analyzing the turbidity of raw water, the effluents of each treatment unit, and the final production water.The evaluation results indicated that, in some instances, the turbidity in production water did not meet the required quality standards. Additionally, it was found that one unit within Karangpilang II WTP, namely the pre-sedimentation unit, exhibited inadequate performance in turbidity removal.Several solutions are proposed to address the turbidity removal issue at Karangpilang II WTP: increasing the maintenance schedule for the pre-sedimentation unit, determining the appropriate turbidity reference for coagulant dosing, optimizing the coagulant dose, utilizing sludge from water treatment as a coagulant aid alongside Al2(SO4)3, and using capping material in the filter unit.